Water management in transition? : investigating the underlying reasons of low level of public participation in water planning in Hungary - Martin, Anna (SLU/Dept. of Urban and Rural Development, 2018)
This thesis examines how the Water Framework Directive has been implemented in Hungary with a particular focus on public participation. Hungary with its heavily centralized water management is relatively new to deliberative approaches, so it is interesting to assess how the country is dealing with a piece of legislation, which requires decentralized steering during the making (planning, reviewing, updating) of the river basin management plans. The qualitative research was based on the semistructured interviews to identify and explore the underlying reasons of the low level of participative potential in the country. During the investigations, the key concept of deliberative democracy served as a theoretical framework.